2023
DOI: 10.1111/joim.13720
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive dysfunction in post‐COVID‐19 condition: Mechanisms, management, and rehabilitation

Marika Möller,
Kristian Borg,
Christer Janson
et al.

Abstract: The long‐term effects of COVID‐19 on cognitive function have become an area of increasing concern. This paper provides an overview of characteristics, risk factors, possible mechanisms, and management strategies for cognitive dysfunction in post‐COVID‐19 condition (PCC).Prolonged cognitive dysfunction is one of the most common impairments in PCC, affecting between 17% and 28% of the individuals more than 12 weeks after the infection and persisting in some cases for several years. Cognitive dysfunctions can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 167 publications
0
6
0
Order By: Relevance
“…Long-term cognitive dysfunction is one of the most common impairments of Long COVID, affecting 17% to 28% of people [ 13 ]. A previous meta-analysis reported that 38.3% of individuals who recovered from COVID-19 self-reported cognitive deficits [ 11 ].…”
Section: Covid-19 Related Cognitive Changes: Prevalence and Manifesta...mentioning
confidence: 99%
“…Long-term cognitive dysfunction is one of the most common impairments of Long COVID, affecting 17% to 28% of people [ 13 ]. A previous meta-analysis reported that 38.3% of individuals who recovered from COVID-19 self-reported cognitive deficits [ 11 ].…”
Section: Covid-19 Related Cognitive Changes: Prevalence and Manifesta...mentioning
confidence: 99%
“…Among the PCC symptoms, prolonged cognitive dysfunction is one of the most common impairments affecting between 17 and 28% of the individuals, and in some cases, persisting for several years. Cognitive dysfunction, commonly observed in these patients, often includes memory impairment, attention deficit, and executive dysfunction where research has revealed a significant reduction in gray matter volume, impaired hippocampal neurogenesis, a decrease in oligodendrocytes and myelin loss causing a reduction in global brain size [39][40][41]. Chronic fatigue syndrome also recurs in patients with PCC and is characterized by immunological, neurological, and gastrointestinal alterations similar to Epstein-Barr virus (EBV)-acquired immunodeficiency in myalgic encephalomyelitis, suggesting the possibility that this virus is related to PCC [42][43][44][45].…”
Section: Neuroinflammation and Oxidative Stress In The Pccmentioning
confidence: 99%
“…[21] Viral infections can indirectly impact episodic memory by reducing the attention and processing speed necessary for encoding. [23] Cognitive exams were done during annual monitoring visits; therefore, the timing of the test administration differed for each participant. Participants included in this analysis had ≥2 assessments during the study period, with ≥1 before and ≥1 after the onset of COVID-19 symptoms.…”
Section: Cognitive Function Assessmentmentioning
confidence: 99%